Hubungan Obesitas dengan Kejadian Hipertensi di Wilayah Kerja Puskesmas Sidomulyo Rawat Inap - Asyfah Asyfah; Usraleli Usraleli; Magdalena Magdalena; Sakhnan Sakhnan; Melly Melly (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Obesity is a condition where excessive accumulation of body fat tissue can cause serious health problems such as hypertension. Obesity and hypertension is a multifactorial disease. Imbalance between consumption of calories and energy needs stored in the form of fat which causes inactive fat tissue so that increased work heart load. As a result of obesity, sufferers tend to suffer from cardiovascular disease. Objective: To determine the relationship of obesity to hypertension in the work area of Sidomulyo Community Health Center. Method: This study is descriptive analytical, conducted on 92 respondents who had a Body Mass Index (BMI)> 23.0. In this study, researchers conducted observations regarding the physical shape of the respondents who came to the elderly polyclinic to check their health, the researcher then asked for approval whether the respondent was willing to be examined for height and weight and blood pressure checked. Results: Of the 18 respondents who were pre-obese, 17 respondents (18.5%) had hypertension and 1 respondent (1.1%) had no hypertension. While from 74 respondents who were obese, 52 respondents (56.5%) had hypertension and 22 respondents (23.9%) had no hypertension. The statistical test used was the chi square test (p = 0.036).  Conclusion: There is a significant relationship between Obesity and Hypertension in the Sidomulyo Community Health Center Working Area. Suggestion: Awareness of the importance of healthy living with an ideal body weight is the main key to fighting obesity and preventing it early.